Pengaruh Kepuasan Kerja dan Stres Kerja terhadap Turnover Intention pada Divisi Culinary Mandapa, A Ritz-Carlton Reserve Ubud, Bali - Ni Luh Ketut Sri Sulistyawati; Ni Putu Shintia Wedani; I Nyoman Gede Mas Wiartha (JURNAL BISNIS HOSPITALITI, 2020)
Turnover intention is very much avoided by companies because it can create instability for labor conditions in the company. Turnover intention can be caused by factors of age, length of work, environmental factors, job stress, and job satisfaction. Mandapa, a Ritz-Carlton Reserve has made various efforts to ensure employee job satisfaction, however, there are many complaints that employees experience regarding workloads that are felt to be quite heavy, causing work stress. Overall, the culinary division has the highest turnover rate compared to other divisions. The population and sample in this study were 50 employees of the culinary division. Methods of data collection using interviews, questionnaires, documentation and observation. Data analysis used quantitative descriptive analysis. The results of multiple linear regression obtained the equation Y = 0.655 - 0.246X1 + 0.399X2. Based on the t test, job satisfaction partially has a negative and significant effect on turnover intention and job stress partially has a positive and significant effect on turnover intention. The results of the determination analysis show that simultaneously job satisfaction and job stress have a contribution of 47% to turnover intention.